Development of CNS metastases and survival in patients with inflammatory breast cancer. Issue 11 (26th March 2018) - Uemura, Marc I.; French, John T.; Hess, Kenneth R.; Liu, Diane; Raghav, Kanwal; Hortobagyi, Gabriel N.; Arun, Banu K.; Valero, Vicente; Ueno, Naoto T.; Alvarez, Ricardo H.; Woodward, Wendy A.; Debeb, Bisrat G.; et al.
Abstract : BACKGROUND: Inflammatory breast cancer (IBC) is associated with a poor prognosis and high risk of central nervous system (CNS) metastases. METHODS: We retrospectively reviewed stage III‐IBC patients compared with noninflammatory invasive ductal carcinoma (NI‐IDC) patients treated between January 1, 1984, and December 31, 2011, who began primary treatment within 1 year of diagnosis and had been followed up for at least 1 year before the development of CNS metastasis or death. Cumulative CNS metastasis incidence and post‐CNS metastasis overall survival (OS) estimates were computed. Multivariable Cox proportional hazard models explored factors for post‐CNS metastasis survival. RESULTS: A total of 2323 patients were identified (589‐IBC/1734‐NI‐IDC). Eighty‐one IBC patients developed CNS metastasis, versus 154 NI‐IDC patients. The 2‐, 5‐, and 10‐year cumulative CNS metastasis incidence rates in IBC and NI‐IDC were 9.8%, 15.8%, 17.4% and 6.5%, 10.1%, and 12.7%, respectively. This was significantly different between IBC and NI‐IDC patients ( P = .0037). Multicovariate competing risk regression models in IBC and NI‐IDC patients showed no statistically significant associations with the risk of developing CNS metastasis, except neoadjuvant taxane use in NI‐IDC patients (hazard ratio, 0.45; 95% confidence interval, 0.24‐0.83; P = .011). The median follow‐up was 7.2 years, and the median post‐CNS metastasis OS was not significantly different between IBC (7.6 months) and NI‐IDC (5.6 months) patients. One hundred ninety patients with CNS metastasis died. HER2‐positive patients had better OS, with a median 14.1 versus 4.3 months ( P < .0001). Age >50 years ( P = .012) but not IBC status was a significant predictor of post‐CNS metastasis survival. CONCLUSION: IBC patients demonstrated higher CNS metastasis incidence rates but OS following CNS metastases is similar in both groups. HER2 status and age may play prognostic roles. Cancer 2018;124:2299‐305 . © 2018 American Cancer Society . Abstract : The largest review of a staged matched cohort of inflammatory breast cancer (IBC) patients versus noninflammatory invasive ductal carcinoma patients reveals that IBC patients have a higher cumulative incidence of central nervous system (CNS) metastases but similar overall survival after CNS metastases development. HER2 status and age may be prognostic.